Dampak Teknologi Terhadap Hubungan Hukum Konsumen dan Pelaku Usaha pada Transaksi E-Commercee Menurut Teori Living Law: Penelitian - Porizky Bernandus Handara Sagal; Agusmidah; Dedi Harianto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The rapid development of information technology has transformed conventional buying and selling transactions into e-commerce platforms. This shift has not only changed business models but has also fundamentally reshaped the legal relationship between consumers and business actors. This study aims to analyze the impact of technological development on the legal relationships between parties in e-commerce transactions by employing a sociology of law approach, particularly Eugen Ehrlich’s Living Law theory. The study uses a juridical-sociological method to observe how norms that emerge and evolve within the e-commerce ecosystem such as Terms of Service (ToS), rating and review mechanisms, and the platform’s internal dispute resolution systems function as a form of “living law.” Ehrlich’s theory is applied to examine the gap between state law such as the Consumer Protection Act and the Electronic Information and Transactions Act (ITE Law) and the actual practices and norms adhered to by the e-commerce community. The findings of this research are expected to demonstrate that the living law created by platforms (platform governance) often has a more direct and effective influence in regulating behavior, building trust, and resolving disputes than state positive law.